The endoplasmic reticulum degradation-enhancing α-mannosidase-like protein 3 attenuates the unfolded protein response and has pro-survival and pro-viral roles in hepatoma cells and hepatocellular carcinoma patients - Alina-Veronica Ghionescu; Mihaela Uta; Andrei Sorop; Catalin Lazar; Petruta R. Flintoaca-Alexandru; Gabriela Chiritoiu; Livia Sima; Stefana-Maria Petrescu; Simona Olimpia Dima; Norica Branza-Nichita (Journal of Biomedical Science)
Abstract Background Chronic hepatitis B virus (HBV) infection is a major risk for development of hepatocellular carcinoma (HCC), a frequent malignancy with a poor survival rate. HBV infection results in significant endoplasmic reticulum (ER) stress and activation of the unfolded protein response (UPR) signaling, a contributing factor to carcinogenesis. As part of the UPR, the ER-associated degradation (ERAD) pathway is responsible for removing the burden of misfolded secretory proteins, to re-establish cellular homeostasis. Emerging evidence indicates consistent upregulation of ERAD factors, including members of the ER degradation-enhancing alpha-mannosidase-like protein (EDEM) family in infection and various tumor types. However, the significance of this gene expression pattern in HBV-driven pathology is just beginning to be deciphered. Methods In this study we quantified the expression of the ERAD factor EDEM3, in a cohort of HCC patients with and without HBV infection, and validated our results by analysis of publically available transcriptomic and microarray data sets. We performed mechanistic studies in HepaRG cells with modulated EDEM3 expression to address UPR, ERAD, autophagy and apoptosis signaling, and their consequences on HBV infection. Results Our work revealed significantly elevated EDEM3 expression in HCC tissues irrespective of HBV infection, while the highest levels were observed in tissues from HBV-infected patients. Investigation of published transcriptomic data sets confirmed EDEM3 upregulation in independent HCC patient cohorts, associated with tumor progression, poor survival prognosis and resistance to therapy. EDEM3-overexpressing hepatic cells exhibited attenuated UPR and activated secretory autophagy, which promoted HBV production. Conversely, cell depletion of EDEM3 resulted in significant ER stress inducing pro-apoptotic mechanisms and cell death. Conclusions We provide evidence of major implications of the ERAD pathway in HBV infection and HCC development and progression. Our results suggest that ERAD activation in HBV-infected cells is a protective mechanism against prolonged ER stress, potentially contributing to establishment of chronic HBV infection and promoting tumorigenesis. Developing specific inhibitors for ERAD factors may be an attractive approach to improve efficiency of current antiviral and anticancer therapies.